Desain Media Interaktif Berbasis Android untuk Pembelajaran Qawa’id Siswa Kelas XII di Madrasah Aliyah Muhammadiyah 1 Malang - Magda, Magda; Anwar, Najih (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The quality of the learning component needs to be adjusted to the sophistication of today's technology. This study aims to produce an Android-based interactive media design for qawa'id learning for class XII MA students at MA Muhammadiyah 1 Malang. This research is motivated by the lack of sophisticated learning media used by educators, causing a lack of motivation to learn. This type of research is development research or Research and Development (R&D) with the ADDIE model. Data collection techniques use interviews, documentation, and questionnaires which then the data results are processed using descriptive verbal analysis techniques and product feasibility analysis. Media validation was carried out at the individual test stage with test subjects, namely IT experts, material experts, and media experts, obtaining 71% results with decent categories. A small group test to determine the level of media eligibility, conducted by an Arabic teacher and 10 students, obtained 77% results with the eligibility category. Field test to find a response to the media, with test subjects of 38 students and obtained 80% results in the good categories.